APPLICATION OF INFORMATION TECHNOLOGY THROUGH DESKTOP-BASED APPLICATIONS TO HELP THE OPERATIONAL PRODUCTIVITY OF THE UMKM “KOPI PINGGIR KALI” (KPK) - Ibad, Sholihul (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This research describes the creation of a desktop-based cash register application that aims to increase operational productivity at MSMEs